Features of distribution, coenotic characteristic and the state of coenopopulations Astragalus dasyanthus Pall. in the river Vorskla catchment (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
In the article shown the results of chorological researches, coenotic features and age structure of 9 coenopopulations Astragalus dasyanthus – rare specias, that are listed on the World Red list, European Red list and the Red Book of Ukraine in the steppe cenosis in the river Vorskla catchment (Belgorod region, Russia; Poltava region, Ukraine).
Keywords: Astragalus dasyanthus, the river Vorskla catchment, coenopopulation, age structure, number, density.